Quality Management and Knowledge: two Complementary Approaches (2019)
Quality Management applied to organizations generates better products and services, cost reduction, more satisfied customers and employees, and improved financial performance, which in turn means competitive advantages. However, sometimes the efforts are not enough, because the organizations don’t have a mature organizational culture that guide them to hold the continuous improvement, satisfied customers, reduced duplicity efforts, redesign of processes, team work and closer supplier relationships. Knowledge management understood as the activities related to creation, storage, transference, and usage of organizational knowledge arises as a possible solution to the difficulties acquired by the application of quality management. This paper shows the difficulties and opportunities created by quality management and how these can be avoided and exploited through the implementation of knowledge management strategies.